2019
DOI: 10.21608/mnj.2019.175763
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment Faced by Female Nursing Students During Clinical Practices

Abstract: Nursing students may be exposed to all types of violence in clinical practice places. Aim: The aim of this paper was to assess the sexual harassment faced by female nursing students during the clinical practices. Material and Method: Descriptive design was used. Subjects: All female nursing students, who were enrolled in the first and second classes of the academic year 2014-2015 at the Faculty of Nursing, Sohag University. Their number was (226). Setting: Faculty of Nursing, Sohag University. A structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Sexual harassment in the workplace has a negative impact on one’s job. According to the current study’s findings, sexual harassment is associated with factors that contribute to burnout, such as loss of occupational motivation ( Tollstern Landin et al, 2020 ), job dissatisfaction ( Nielsen et al, 2010 ; Ali and Ezz El Rigal, 2019 ; Maghraby et al, 2020 ), loss of job and negative job effects ( Gabay and Shafran Tikva, 2020 ; Maghraby et al, 2020 ), problems with routine work processes ( Nielsen et al, 2017 ), and negative effects on patient care ( Kim et al, 2018 ; Gabay and Shafran Tikva, 2020 ). Tollstern Landin et al (2020) demonstrated that sexual harassment could be a serious job risk and stigma for nurses in Tanzania, Africa, and an important factor in losing occupational motivation ( Tollstern Landin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Sexual harassment in the workplace has a negative impact on one’s job. According to the current study’s findings, sexual harassment is associated with factors that contribute to burnout, such as loss of occupational motivation ( Tollstern Landin et al, 2020 ), job dissatisfaction ( Nielsen et al, 2010 ; Ali and Ezz El Rigal, 2019 ; Maghraby et al, 2020 ), loss of job and negative job effects ( Gabay and Shafran Tikva, 2020 ; Maghraby et al, 2020 ), problems with routine work processes ( Nielsen et al, 2017 ), and negative effects on patient care ( Kim et al, 2018 ; Gabay and Shafran Tikva, 2020 ). Tollstern Landin et al (2020) demonstrated that sexual harassment could be a serious job risk and stigma for nurses in Tanzania, Africa, and an important factor in losing occupational motivation ( Tollstern Landin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 78%
“…This refers to the psychological problems nurses face because of the negative consequences of sexual harassment in the workplace. Several studies, including this one, have found that sexual harassment can have negative psychological effects such as mental health disorders ( Nielsen et al, 2010 ; Ali and Ezz El Rigal, 2019 ), sadness, shame, and anger ( Tollstern Landin et al, 2020 ). Psychological imbalances can cause severe negative emotions and fear in nurses ( Nielsen et al, 2017 ; Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations